Synthesis of Alkenyl Nitriles by Bidentate Cobalt-Catalyzed Acceptorless Dehydrogenation Coupling of Alcohols and Nitriles - Zhang, Zhaolun; Chen, Sanxia; Tian, Haitao; Tang, Conghui (Synlett, 2025)
A bidentate Co(III)-catalyzed α-oleﬁnation of nitriles has been developed. This one-pot protocol provides a simple procedure for the synthesis of alkenyl nitriles from diverse alcohols and nitriles. An extensive substrate scope, good functional-group compatibility, and high atom economy are displayed. Preliminary mechanistic studies revealed that C=C bond formation proceeds through activation of the O–H bond of the alcohol via an unsaturated 16-electron intermediate cobalt complex, and subsequent condensation of the in situ-formed aldehyde with the nitrile. Remarkably, this method liberates H2 and H2O as the only byproducts.
Keywords: cobalt catalysis; dehydrogenation; alkenyl nitriles; oleﬁnation; nitriles; alcohols